A ring-type double-helix electrochemical device and application method

Through the application of the ring-type double helix electrochemical device, the use of electric fields and heat to treat heavy metal ions in industrial wastewater, and efficient removal and resource recycling are achieved, solving the problems of low efficiency and high cost of heavy metal treatment in the prior art.

CN119143249BActive Publication Date: 2025-04-29CHANGSHA ENVIRONMENTAL PROTECTION COLLEGE +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411332170.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-04-29
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove and recover heavy metal ions in industrial wastewater, and physical and chemical methods lead to high salinity of treated wastewater, affecting biochemical properties, and generating a large amount of sludge, increasing recycling costs.

Method used

A ring-type double helix electrochemical device is adopted, including an inner helix electrode, an outer helix electrode, a quantum dot active electrode and a magnetic stirrer. The homogenization electric field and heat are formed through a DC power supply and an AC power supply to achieve the reduction and precipitation of heavy metal ions, and the heavy metal precipitation is recovered through magnetic stirring and sludge scraping components.

Benefits of technology

It realizes efficient removal and resource recycling of heavy metal wastewater, reduces the salinity of the treated wastewater, reduces sludge generation, reduces recycling costs, and extends the service life of the quantum dot active electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143249B_ABST
    Figure CN119143249B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of electrochemical water treatment and resource recovery, and specifically to a sleeve-type double-helix electrochemical device and an application method. The electrochemical device comprises a reaction chamber, an inner spiral electrode, an outer spiral electrode, a direct current power supply, a quantum dot active electrode and a magnetic stirrer, wherein the inner spiral electrode and the outer spiral electrode are coaxially sleeved in the reaction chamber; the positive pole of the direct current power supply is connected to the outer spiral electrode, and the negative pole is connected to the inner spiral electrode; the number of quantum dot active electrodes is multiple and all are arranged in the reaction chamber. The electrochemical device also comprises a recovery tank, a sieve plate, a scraper and an alternating current power supply; the recovery tank is arranged below the reaction chamber, and the two are connected through the sieve plate; the magnetic stirrer is arranged on the sieve plate; the scraper can be rotatably arranged in the recovery tank; the positive pole and the negative pole of the alternating current power supply are both connected to the outer spiral electrode. The application method uses the electrochemical device to complete the purification of heavy metal wastewater and the resource recovery of heavy metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical water treatment and resource recovery, and in particular to a sleeve-type double-helix electrochemical device and an application method thereof. Background Art

[0002] With the rapid development of industries such as electroplating, electronics and metallurgy, the problem of heavy metal pollution in discharged industrial wastewater is very prominent. Heavy metal ions in industrial wastewater pose a serious threat to organisms and the environment due to their environmental toxicity, non-biodegradability and persistence. Due to their non-biodegradability and long biological half-life, heavy metals in wastewater cause serious pollution of groundwater, surface water, soil and crops. Therefore, the treatment of heavy metal wastewater is imminent.

[0003] Considering that heavy metals contained in wastewater are also an important resource, heavy metal minerals are non-renewable resources, but hundreds of thousands of tons of heavy metals are discharged into the environment through industrial processes every year, causing a huge waste of resources. Therefore, the treatment and resource recovery of heavy metals in wastewater has positive practical application value and economic value.

[0004] At present, the mainstream method for removing and recycling heavy metals from wastewater is physical and chemical methods. This method requires the addition of a large amount of chemical reagents during the treatment process, which ultimately results in the salinity of the treated wastewater being higher than that of seawater. This not only affects the biodegradability of the wastewater, but also makes it difficult to remove substances such as ammonia nitrogen and total phosphorus in the subsequent treatment process. It also generates a large amount of sludge during the separation of heavy metals, greatly increases the difficulty of reusing wastewater, and further increases the recycling cost.

[0005] Electrochemical treatment is a new technology in sewage treatment. Electrochemical technology can induce and accelerate chemical reactions and has the advantages of being green and efficient. Therefore, the use of electrochemical technology is expected to achieve effective removal and resource recovery of heavy metal wastewater.

[0006] In summary, it is necessary to develop a toroidal double-helix electrochemical device and an application method for removing and recovering heavy metals in wastewater. Summary of the invention

[0007] The present invention aims to provide a ring-type double-helix electrochemical device and an application method. The specific technical scheme is as follows:

[0008] In a first aspect, the present invention provides a sleeve-type double-helix electrochemical device, comprising a reaction chamber, an inner helical electrode, an outer helical electrode, a DC power supply, a quantum dot active electrode, and a magnetic stirrer;

[0009] A water inlet and a feed port are arranged on the top of the reaction chamber, and a water outlet is arranged on one side of the bottom of the reaction chamber; a support column is arranged in the reaction chamber along its axial direction, and the support column is connected to the bottom of the reaction chamber; the inner spiral electrode is arranged in the reaction chamber and sleeved on the outer wall surface of the support column; the outer spiral electrode is arranged in the reaction chamber and coaxially sleeved on the outer side of the inner spiral electrode and connected to the inner wall surface of the reaction chamber; the outer spiral electrode is connected to the positive electrode of the DC power supply, and the inner spiral electrode is connected to the negative electrode of the DC power supply; the number of the quantum dot active electrodes is multiple, and they are all arranged in the reaction chamber; the magnetic stirrer is arranged at the bottom of the reaction chamber.

[0010] Optionally, the sleeve-type double-helix electrochemical device further includes a recovery tank, a sieve plate, a sludge scraping assembly and an AC power supply;

[0011] The recovery tank is arranged below the reaction chamber, and the two are connected through the sieve plate; the magnetic stirrer is arranged on the sieve plate; the scraper assembly includes a scraper blade, a rotating shaft and a driving member; the rotating shaft is rotatably arranged on the axis of the recovery tank, one end of the rotating shaft is arranged in the recovery tank, and the other end passes through the bottom of the recovery tank and is connected to the output end of the driving member; the driving member is arranged on the outside of the bottom of the recovery tank; the scraper blade is arranged in the recovery tank and is connected to the rotating shaft; the end of the scraper blade away from the rotating shaft is arranged toward the inner wall of the recovery tank, and is in contact with the inner wall of the recovery tank or has a gap; a mud discharge port and an adjustment plate for adjusting the opening and closing of the mud discharge port and the size of the opening are arranged on one side wall of the recovery tank; the adjustment plate is rotatably arranged on the mud discharge port; the positive and negative electrodes of the AC power supply are both connected to the outer spiral electrode.

[0012] Optionally, the reaction chamber further comprises a cover plate detachably arranged on the top thereof, and the water inlet and the feeding port are both arranged on the cover plate; an exhaust hole is also arranged on the cover plate.

[0013] Optionally, the sieve holes on the sieve plate have an aperture range of 0.05 to 0.5 mm.

[0014] In a second aspect, the present invention provides an application method of the loop-type double-helix electrochemical device, comprising:

[0015] Step S1, feeding the quantum dot active electrode into the reaction chamber through the feeding port;

[0016] Step S2, adding heavy metal wastewater into the reaction chamber through the water inlet, controlling the input amount of the quantum dot active electrode to be 1-5 g per liter of the heavy metal wastewater;

[0017] The DC power supply is started so that the inner spiral electrode and the outer spiral electrode form a homogenized electric field; the magnetic stirrer is started so that the quantum dot active electrode is evenly dispersed in the heavy metal wastewater, and the heavy metal ions in the heavy metal wastewater are reduced to form heavy metal precipitates and purified water; wherein the purified water is discharged through the water outlet, and the heavy metal precipitates are adsorbed in the pores of the quantum dot active electrodes;

[0018] Step S3, repeating step S2 for 20 to 30 times, when the quantum dot active electrode is saturated or nearly saturated with the adsorption of heavy metal precipitates, adding liquid medium into the reaction chamber through the water inlet; starting the magnetic stirrer to stir until the quantum dot active electrode and the liquid medium are mixed; starting the AC power supply so that the outer spiral electrode generates heat to break the quantum dot active electrode, and the heavy metal precipitates adsorbed by the quantum dot active electrode are released and flow into the recovery tank through the sieve plate; settling for 20 to 30 minutes; the liquid medium is discharged through the water outlet, and the heavy metal precipitates are discharged from the mud discharge port through the action of the mud scraping component.

[0019] Optionally, the heavy metal ions in the heavy metal wastewater include at least one of Tl ions, Cr ions, Pb ions, Cd ions and Cu ions;

[0020] In step S2, the voltage range of the DC power supply is 2 to 5 V / cm, and the operation time is 30 to 60 min; the speed of the magnetic stirrer is 100 to 150 rpm;

[0021] In step S3, the voltage range of the AC power supply is 220-380 V / cm, and the operating time is 1-2 h; the rotation speed of the magnetic stirrer is 200-300 rpm; the liquid medium includes pure water, tap water and salt solution; the molar concentration of the salt solution (such as sodium sulfate solution) is 0.05-0.2 M.

[0022] Optionally, the application method further comprises preparing the quantum dot active electrode, and the preparation method thereof is as follows:

[0023] Step A1, after mixing the prepared carbon quantum dots and the prepared oxidized cellulose solution, add them into a flask, then add acetic acid, heat and react, condense and reflux and stir during the reaction; filter the liquid after the reaction with a dialysis bag, collect the liquid in the dialysis bag, and obtain a carbon quantum dot-cellulose network;

[0024] Step A2, adding the carbon quantum dot-cellulose network into a dimethyl sulfoxide solution and stirring evenly; then, adding polyvinyl alcohol and heating for reaction, after the reaction is completed, injecting the reaction liquid into a mold, freeze-thawing and forming, to obtain a quantum dot active electrode.

[0025] Optionally, in step A1, the method for preparing the carbon quantum dots is as follows: 1.5-2.5 g of citric acid, 50-100 mg of iron oxide and 0.1-0.5 mL of ethylenediamine are added to 15-25 mL of deionized water, and a mixed solution is obtained by ultrasonic treatment; then, the mixed solution is heated to react at 180-220° C. for 1-2 hours; after the mixed solution after the reaction is cooled to room temperature, it is dialyzed for 36-48 hours using a dialysis bag with a pore size of 500-1000 Da; the liquid in the dialysis bag is collected and dried to obtain the carbon quantum dots; wherein the ultrasonic time used is 10-30 min, and the ultrasonic frequency is 40 KHz;

[0026] In step A1, the method for preparing the oxidized cellulose solution is as follows: 1-2 g of sodium periodate is dissolved in 90-110 mL of a cellulose solution with a concentration of 2-3 wt%, after mixing in a dark environment, 0.5-1.0 mL of ethylene glycol is added, and the mixture is stirred at 100-150 rpm, and the liquid is collected and filtered through a dialysis bag with a pore size of 8-14 kDa; the dialysis water is replaced once per dialysis day, and the dialysis is performed for 4-7 days, and the liquid in the dialysis bag is collected to obtain the oxidized cellulose solution.

[0027] Optionally, in step A1, when preparing the carbon quantum dot-cellulose network, the amount of the carbon quantum dots is 20 to 50 mg; the amount of the oxidized cellulose solution is 18 to 22 g; the carbon quantum dots and the oxidized cellulose solution are stirred during mixing, the stirring speed is 100 to 150 rpm, and the stirring time is 30 to 60 min; the amount of acetic acid is 0.2 to 0.6 mL; the temperature used during the heating reaction is 80 to 90° C., and the reaction time is 4 to 6 h; the pore size of the dialysis bag used is 8 to 14 kDa, and the dialysis time is 2 to 4 d.

[0028] Optionally, in step A2, when preparing the quantum dot active electrode, the amount of the carbon quantum dot-cellulose network used is 6 to 10 g, and the amount of the dimethyl sulfoxide used is 10 to 14 g; when the carbon quantum dot-cellulose network and the dimethyl sulfoxide solution are stirred evenly, the stirring speed used is 100 to 150 rpm, and the stirring time is 30 to 60 min; the amount of polyvinyl alcohol used is 1.5 to 2.0 g; the temperature used during the heating reaction is 80 to 100°C, and the reaction time is 4 to 6 h; the temperature used for freeze-thaw is -4 to -20°C.

[0029] The application of the technical solution of the present invention has at least the following beneficial effects:

[0030] (1) The present invention provides a ring-shaped double-helix electrochemical device and an application method, which can efficiently reduce and remove heavy metal ions in heavy metal wastewater, thereby achieving the effect of water purification. Specifically, a quantum dot active electrode is added into the reaction chamber through a feeding port, and heavy metal wastewater is added into the reaction chamber through a water inlet, and the amount of quantum dot active electrode added is controlled to be 1 to 5 g per liter of heavy metal wastewater; the magnetic stirrer is started so that the quantum dot active electrode is evenly dispersed in various positions of the heavy metal wastewater in the reaction chamber; an inner spiral electrode is arranged along the axial direction in the reaction chamber, and an outer spiral electrode is coaxially sleeved on the outer side of the inner spiral electrode and connected to the wall surface of the reaction chamber, and electric field homogenization can be achieved under the action of a direct current power supply, so that the quantum dot active electrode can exert the best electrocatalytic activity at various positions of the heavy metal wastewater in the reaction chamber, and the removal efficiency of heavy metals is improved by an order of magnitude, which greatly shortens the processing time; wherein, the quantum dot active electrode reduces the heavy metal ions in the heavy metal wastewater to form heavy metal precipitates and purified water; wherein, the purified water is discharged through a water outlet, and the heavy metal precipitates are adsorbed in the pores of the quantum dot active electrode; a support column is used to fix the inner spiral electrode and improve its stability.

[0031] (2) The present invention provides a sleeve-type double-helix electrochemical device and application method, which can also recover heavy metal precipitates and realize the reuse of heavy metal resources. Specifically, when the quantum dot active electrode is saturated or close to saturation in adsorbing heavy metal precipitates, a liquid medium is added into the reaction chamber through the water inlet; the magnetic stirrer is started to stir until the quantum dot active electrode and the liquid medium are mixed; the AC power supply is started to generate heat at the outer spiral electrode, and the heat is transferred to the quantum dot active electrodes uniformly dispersed at various positions in the liquid medium through the heat conduction of the liquid medium, so that each quantum dot active electrode is broken by heat, and the heavy metal precipitates adsorbed by the quantum dot active electrode are released and flow into the recovery pool through the sieve plate; the heavy metal precipitates are discharged from the mud outlet through the action of the mud scraping component, and the heavy metal precipitates can be recovered to realize the reuse of heavy metal resources.

[0032] (3) In the present invention, when preparing the quantum dot active electrode, carbon quantum dots and cellulose are heated to produce Schiff base reaction to form a connected carbon quantum dot-cellulose network, thereby avoiding the precipitation of carbon quantum dots. At the same time, polyvinyl alcohol is used in combination, which can more effectively wrap the carbon quantum dot-cellulose network, effectively inhibit the precipitation of carbon quantum dots in the quantum dot active electrode, and extend the service life of the quantum dot active electrode, so that the quantum dot active electrode prepared by the present invention has a stronger heavy metal removal and enrichment ability, laying an important foundation for the recovery of heavy metal resources. The carbon quantum dots in the quantum dot active electrode prepared in the present invention can generate a large amount of oxygen active substances (such as hydroxyl radicals, superoxide radicals and singlet oxygen, etc.) in the electric field. These oxygen active substances can be bound by the iron oxide in the quantum dot active electrode through electromagnetic action inside the quantum dot active electrode due to their lone electrons, thereby increasing the local oxygen active substance concentration in the quantum dot active electrode; the oxygen active substances contact and react with heavy metal ions, promoting the heavy metal ions to form an easily precipitated form to achieve heavy metal wastewater purification. In addition, under the action of a DC electric field, the carbon quantum dots in the quantum dot active electrode can form an electron-rich reduction zone at one end, and the heavy metal ions are in direct contact with the reduction zone, and a continuous electron transfer process occurs to obtain the reduced heavy metal element and precipitate. In addition, after starting the AC power supply, the outer spiral electrode not only generates heat, but also dissolves and breaks the polyvinyl alcohol structure of the quantum dot active electrode, thereby releasing the catalytic core and heavy metal precipitate contained in the quantum dot active electrode; after starting the AC power supply, the outer spiral electrode also generates a magnetic field, and the iron oxide contained in the catalytic core is attached to the surface of the outer spiral electrode by magnetic force, so as to separate the catalytic core from the heavy metal precipitate, and facilitate the reuse of the catalytic core (such as preparing the quantum dot active electrode again) and the reuse of the heavy metal.

[0033] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0035] Figure 1 It is a schematic structural diagram of a ring-type double-helix electrochemical device in Example 1 of the present invention;

[0036] Figure 2 It is a schematic diagram of the connection between the inner spiral electrode, the outer spiral electrode, the DC power supply and the AC power supply;

[0037] Figure 3 yes Figure 1A top view of the water inlet (the water regulating valve on the water inlet, the water outlet and the water regulating valve on the water outlet are not shown in the figure);

[0038] Figure 4 is a top view of Comparative Example 1;

[0039] Figure 5 2 are two spiral electrode structures in Example 1 and Comparative Example 1 and corresponding electric field intensity distribution diagrams;

[0040] Among them, 1. reaction chamber, 1.1. water inlet, 1.2. feeding port, 1.3. water outlet, 1.4. exhaust hole, 2. inner spiral electrode, 3. outer spiral electrode, 4. DC power supply, 5. quantum dot active electrode, 6. recovery tank, 6.1. adjustment plate, 7. sieve plate, 8. AC power supply, 9. scraper, 10. magnetic stirrer. DETAILED DESCRIPTION

[0041] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0042] Embodiment 1:

[0043] See also Figure 1-Figure 3 A sleeve-type double-helix electrochemical device, comprising a reaction chamber 1, an inner spiral electrode 2 (made of ruthenium-iridium-titanium alloy or stainless steel; specifically, ruthenium-iridium-titanium alloy can be selected, and the alloy implementation standard adopted is HG / T2471-2011 standard), an outer spiral electrode 3 (made of nickel-chromium alloy, specifically Cr20Ni80 model), a DC power supply 4, a quantum dot active electrode 5 and a magnetic stirrer 10;

[0044] A water inlet 1.1 and a feeding port 1.2 are arranged on the top of the reaction chamber 1, and a water outlet 1.3 is arranged on one side of the bottom of the reaction chamber 1; regulating water valves are arranged on the water inlet 1.1 and the water outlet 1.3; a support column (not shown in the figure) is arranged in the reaction chamber 1 along its axial direction, and the support column is connected to the bottom of the reaction chamber 1; the inner spiral electrode 2 is arranged in the reaction chamber 1 and is sleeved on the outer wall surface of the support column; the outer spiral electrode 3 is arranged in the reaction chamber 1, and is coaxially sleeved on the outer side of the inner spiral electrode 2 and connected to the inner wall surface of the reaction chamber 1; the outer spiral electrode 3 is connected to the positive electrode of the DC power supply 4, and the inner spiral electrode 2 is connected to the negative electrode of the DC power supply 4; the number of the quantum dot active electrodes 5 is multiple, and they are all arranged in the reaction chamber 1; the magnetic stirrer 10 is arranged at the bottom of the reaction chamber 1.

[0045] The sleeve-type double-helix electrochemical device also includes a recovery tank 6, a sieve plate 7, a sludge scraping assembly and an AC power supply 8;

[0046] The recovery tank 6 is arranged below the reaction chamber 1, and the two are connected through the sieve plate 7; the magnetic stirrer 10 is arranged on the sieve plate 7; the scraper assembly includes a scraper blade 9, a rotating shaft (not shown in the figure) and a driving member (not shown in the figure); the rotating shaft is rotatably arranged on the axis of the recovery tank 6, one end of the rotating shaft is arranged in the recovery tank 6, and the other end passes through the bottom of the recovery tank 6 and is connected to the output end of the driving member; the driving member is arranged on the outside of the bottom of the recovery tank 6; the scraper blade 9 is arranged in the recovery tank 6 and is connected to the rotating shaft; the end of the scraper blade 9 away from the rotating shaft is arranged toward the inner side wall of the recovery tank 6 and is connected to the output end of the driving member The inner wall of the recovery pool 6 is fitted or has a gap; specifically, when the material of the scraper blade 9 is relatively soft, such as a soft plastic plate, it can fit the inner wall of the recovery pool 6 to ensure that the heavy metal precipitation on the inner wall of the recovery pool 6 is scraped off; when the material of the scraper blade 9 is relatively hard, such as a hard plastic plate, a gap of 0.01-1mm can be left with the inner wall of the recovery pool 6, which can avoid damaging the inner wall of the recovery pool 6 and can be relatively scraped off; a mud discharge port and an adjustment plate 6.1 for adjusting the opening and closing of the mud discharge port and the size of the opening are set on one side wall of the recovery pool 6; the adjustment plate 6.1 can be rotatably set on the mud discharge port; the positive and negative electrodes of the AC power supply 8 are both connected to the outer spiral electrode 3.

[0047] The reaction chamber 1 also includes a cover plate detachably arranged on the top thereof, which is convenient for cleaning and maintenance of the reaction chamber 1 and for installing the support column and the inner spiral electrode 2; the water inlet 1.1 and the feed port 1.2 are both arranged on the cover plate; an exhaust hole 1.4 is also arranged on the cover plate to facilitate timely discharge of excess gas in the reaction chamber 1.

[0048] The aperture range of the sieve holes on the sieve plate 7 is 0.05 mm.

[0049] An application method of the loop-type double-helix electrochemical device comprises:

[0050] Step S1, feeding the quantum dot active electrode 5 into the reaction chamber 1 through the feeding port 1.2;

[0051] Step S2, adding heavy metal wastewater into the reaction chamber 1 through the water inlet 1.1, and controlling the input amount of the quantum dot active electrode 5 to be 1g per liter of the heavy metal wastewater;

[0052] The DC power supply 4 is started (voltage 2V / cm, operation 30min), so that the inner spiral electrode 2 and the outer spiral electrode 3 form a homogenized electric field; the magnetic stirrer 10 is started (rotation speed is 100rpm), so that the quantum dot active electrode 5 is evenly dispersed in the heavy metal wastewater, and the heavy metal ions in the heavy metal wastewater are reduced to form heavy metal precipitates and purified water; wherein the purified water is discharged through the water outlet 1.3, and the heavy metal precipitates are adsorbed in the pores of the quantum dot active electrode 5;

[0053] Step S3, repeating step S2 to 20 times, when the quantum dot active electrode 5 is saturated or nearly saturated with the adsorption of heavy metal precipitates, adding 0.05M sodium sulfate solution into the reaction chamber 1 through the water inlet 1.1; starting the magnetic stirrer 10 to stir (at a speed of 200rpm) until the quantum dot active electrode 5 and the sodium sulfate solution are mixed; starting the AC power supply 8 (voltage 220V, running for 1h), so that the outer spiral electrode 3 generates heat to break the quantum dot active electrode 5, and the heavy metal precipitates adsorbed by the quantum dot active electrode 5 are released and flow into the recovery tank 6 through the sieve plate 7; precipitate for 20min; the sodium sulfate solution is discharged through the water outlet 1.3, and the heavy metal precipitates are discharged from the mud discharge port through the action of the mud scraping component.

[0054] The application method further includes preparing the quantum dot active electrode 5, and the preparation method is as follows:

[0055] Step A1, after mixing the prepared carbon quantum dots and the prepared oxidized cellulose solution, add them into a single-necked flask, then add acetic acid, heat in an oil bath for reaction, condense reflux and stir during the reaction; filter the liquid after the reaction with a dialysis bag, collect the liquid in the dialysis bag, and obtain a carbon quantum dot-cellulose network;

[0056] Step A2, adding the carbon quantum dot-cellulose network into the dimethyl sulfoxide solution and stirring evenly; then, adding polyvinyl alcohol and heating for reaction, after the reaction is completed, injecting the reaction liquid into a plastic mold, freeze-thaw forming, and obtaining a quantum dot active electrode 5.

[0057] In step A1, the method for preparing the carbon quantum dots is as follows: 1.5 g of citric acid, 50 mg of iron oxide and 0.1 mL of ethylenediamine are added to 15 mL of deionized water, and a mixed solution is obtained by ultrasonic treatment; then, the mixed solution is heated at 180° C. for 1 h; after the mixed solution after the reaction is cooled to room temperature, it is dialyzed for 36 h using a dialysis bag with a pore size of 500 Da; the liquid in the dialysis bag is collected and dried to obtain the carbon quantum dots; wherein the ultrasonic time used is 10 min and the ultrasonic frequency is 40 KHz;

[0058] In step A1, the method for preparing the oxidized cellulose solution is as follows: 1 g of sodium periodate is dissolved in 90 mL of a cellulose solution with a concentration of 2 wt%, after mixing in a dark place, 0.5 mL of ethylene glycol is added, and the mixture is stirred at 100 rpm, and the liquid is collected and filtered through a dialysis bag with a pore size of 8 kDa; the dialysis water is replaced once every dialysis day, and the dialysis is performed for 4 days, and the liquid in the dialysis bag is collected to obtain the oxidized cellulose solution.

[0059] In step A1, when preparing the carbon quantum dot-cellulose network, the amount of the carbon quantum dots is 20 mg; the amount of the oxidized cellulose solution is 18 g; the carbon quantum dots and the oxidized cellulose solution are stirred for mixing, the stirring speed is 100 rpm, and the stirring time is 30 min; the amount of acetic acid is 0.2 mL; the temperature used in the heating reaction is 80° C., and the reaction time is 4 h; the pore size of the dialysis bag used is 8 kDa, and the dialysis time is 2 d.

[0060] In step A2, when preparing the quantum dot active electrode 5, the amount of the carbon quantum dot-cellulose network used is 6 g, and the amount of the dimethyl sulfoxide used is 14 g; when the carbon quantum dot-cellulose network and the dimethyl sulfoxide solution are stirred evenly, the stirring speed used is 100 rpm, and the stirring time is 30 min; the amount of polyvinyl alcohol used is 1.5 g; the temperature used during the heating reaction is 80°C, and the reaction time is 4 h; the temperature used for freeze-thaw is -4°C.

[0061] Embodiment 2:

[0062] The difference from Example 1 is:

[0063] The aperture range of the sieve holes on the sieve plate 7 is 0.28 mm.

[0064] In step A1, the method for preparing the carbon quantum dots is as follows: 2 g of citric acid, 75 mg of iron oxide and 0.3 mL of ethylenediamine are added to 20 mL of deionized water, and a mixed solution is obtained by ultrasonic treatment; then, the mixed solution is heated at 200° C. for reaction for 1.5 h; after the mixed solution after the reaction is cooled to room temperature, it is dialyzed for 42 h using a dialysis bag with a pore size of 750 Da; the liquid in the dialysis bag is collected and dried to obtain the carbon quantum dots; wherein the ultrasonic time used is 20 min;

[0065] In step A1, the method for preparing the oxidized cellulose solution is as follows: 1.5 g of sodium periodate is dissolved in 100 mL of a cellulose solution with a concentration of 2.5 wt %, and after mixing in the dark, 0.75 mL of ethylene glycol is added, and the mixture is stirred and mixed at 125 rpm, and the liquid is collected and filtered through a dialysis bag with a pore size of 11 kDa; the dialysis water is replaced once every dialysis day, and the dialysis is performed for 5.5 days, and the liquid in the dialysis bag is collected to obtain the oxidized cellulose solution.

[0066] In step A1, when preparing the carbon quantum dot-cellulose network, the amount of the carbon quantum dots is 35 mg; the amount of the oxidized cellulose solution is 20 g; the carbon quantum dots and the oxidized cellulose solution are stirred for mixing, the stirring speed is 125 rpm, and the stirring time is 45 min; the amount of acetic acid is 0.4 mL; the temperature used in the heating reaction is 85° C., and the reaction time is 5 h; the pore size of the dialysis bag used is 11 kDa, and the dialysis time is 3 d.

[0067] In step A2, when preparing the quantum dot active electrode 5, the amount of the carbon quantum dot-cellulose network used is 8 g, and the amount of the dimethyl sulfoxide used is 12 g; when the carbon quantum dot-cellulose network and the dimethyl sulfoxide solution are stirred evenly, the stirring speed used is 125 rpm, and the stirring time is 45 min; the amount of polyvinyl alcohol used is 1.75 g; the temperature used during the heating reaction is 90°C, and the reaction time is 5 h; the temperature used for freeze-thaw is -12°C.

[0068] In step S2, the input amount of the quantum dot active electrode 5 is controlled to be 3 g per liter of the heavy metal wastewater;

[0069] The voltage of the DC power supply 4 is 3.5 V / cm, and the operation time is 45 min. The rotation speed of the magnetic stirrer 10 is 120 rpm.

[0070] In step S3, steps S2 to S3 are repeated 25 times, the molar concentration of the sodium sulfate solution is 0.125 M; the stirring speed of the magnetic stirrer 10 is 250 rpm; the voltage of the AC power supply 8 is 300 V, and it runs for 1.5 hours; and the precipitation is carried out for 25 minutes.

[0071] Embodiment 3:

[0072] The difference from Example 1 is:

[0073] The aperture range of the sieve holes on the sieve plate 7 is 0.5 mm.

[0074] In step A1, the method for preparing the carbon quantum dots is as follows: 2.5 g of citric acid, 100 mg of iron oxide and 0.5 mL of ethylenediamine are added to 25 mL of deionized water, and a mixed solution is obtained by ultrasonic treatment; then, the mixed solution is heated at 220° C. for reaction for 2 h; after the mixed solution after the reaction is cooled to room temperature, it is dialyzed for 48 h using a dialysis bag with a pore size of 1000 Da; the liquid in the dialysis bag is collected and dried to obtain the carbon quantum dots; wherein the ultrasonic time used is 30 min;

[0075] In step A1, the method for preparing the oxidized cellulose solution is as follows: 2 g of sodium periodate is dissolved in 110 mL of a cellulose solution with a concentration of 3 wt%, and after mixing in the dark, 1.0 mL of ethylene glycol is added, and the mixture is stirred and mixed at 150 rpm, and the liquid is collected and filtered through a dialysis bag with a pore size of 14 kDa; the dialysis water is replaced once every dialysis day, and the dialysis is performed for 7 days, and the liquid in the dialysis bag is collected to obtain the oxidized cellulose solution.

[0076] In step A1, when preparing the carbon quantum dot-cellulose network, the amount of the carbon quantum dots is 50 mg; the amount of the oxidized cellulose solution is 22 g; the carbon quantum dots and the oxidized cellulose solution are stirred for mixing, the stirring speed is 150 rpm, and the stirring time is 60 min; the amount of acetic acid is 0.6 mL; the temperature used in the heating reaction is 90° C., and the reaction time is 6 h; the pore size of the dialysis bag used is 14 kDa, and the dialysis time is 4 d.

[0077] In step A2, when preparing the quantum dot active electrode 5, the amount of the carbon quantum dot-cellulose network used is 10g, and the amount of the dimethyl sulfoxide used is 10g; when the carbon quantum dot-cellulose network and the dimethyl sulfoxide solution are stirred evenly, the stirring speed used is 150rpm, and the stirring time is 60min; the amount of polyvinyl alcohol used is 2.0g; the temperature used during the heating reaction is 100°C, and the reaction time is 6h; the temperature used for freeze-thaw is -20°C.

[0078] In step S2, the input amount of the quantum dot active electrode 5 is controlled to be 5 g per liter of the heavy metal wastewater;

[0079] The voltage of the DC power supply 4 is 5 V / cm, and the operation time is 60 min. The rotation speed of the magnetic stirrer 10 is 150 rpm.

[0080] In step S3, step S2 is repeated 30 times, the molar concentration of the sodium sulfate solution is 0.2M; the stirring speed of the magnetic stirrer 10 is 300rpm; the voltage of the AC power supply 8 is 380V, and it runs for 2h; and the precipitation is 30min.

[0081] Comparative Example 1:

[0082] The difference from Example 1 is that: Figure 4-Figure 5 As shown, the reaction chamber 1 is not provided with a sleeve of an inner spiral electrode 2 and an outer spiral electrode 3 , but two parallel inner spiral electrodes 2 are provided on both sides of the axial direction in the reaction chamber 1 .

[0083] Comparative Example 2:

[0084] The difference from Example 1 is that no carbon quantum dots are added in the preparation of the quantum dot active electrode 5 .

[0085] Comparative Example 3:

[0086] The difference from Example 1 is that no iron oxide is added in the preparation of the quantum dot active electrode 5 .

[0087] Comparative Example 4:

[0088] The difference from Example 1 is that when preparing the carbon quantum dot-cellulose network in step A1, the heating reaction of the carbon quantum dots and the oxidized cellulose solution is cancelled and a room temperature reaction is adopted.

[0089] Comparative Example 5:

[0090] The difference from Example 1 is that no quantum dot active electrode 5 is added.

[0091] Comparative Example 6:

[0092] The difference from Embodiment 1 is that no electric field is applied, that is, the DC power supply 4 and the AC power supply 8 are not started.

[0093] The heavy metal wastewater used in Examples 1 to 3 and Comparative Examples 1 to 6 of the present invention is artificially simulated heavy metal wastewater. The specific simulation conditions are as follows:

[0094] In the simulated heavy metal wastewater, the Tl content was 1 mg / L, the Cr content was 50 mg / L, the Pb content was 1 mg / L, the Cd content was 20 mg / L and the Cu content was 50 mg / L.

[0095] After the present invention uses the electrochemical device in Examples 1 to 3 and Comparative Examples 1 to 6 to treat artificially simulated heavy metal wastewater, the removal rates and resource recovery rates of various heavy metals in the heavy metal wastewater are shown in Tables 1 and 2 below. Among them, the concentrations of various heavy metals in the heavy metal wastewater are measured using inductively coupled plasma mass spectrometry, referring to HJ700-2014. The resource recovery rate of heavy metals in the heavy metal wastewater is determined by combining aqua regia digestion and inductively coupled plasma mass spectrometry.

[0096] Table 1 Heavy metal removal rate

[0097] Pollutants Tl(%) Cr(%) Pb(%) Cd(%) Cu(%) Example 1 98.79 98.88 97.99 98.25 98.56 Example 2 98.17 98.56 98.58 98.05 99.04 Example 3 99.06 98.68 97.74 98.65 98.18 Comparative Example 1 20.80 14.94 17.88 22.60 24.68 Comparative Example 2 59.29 55.06 57.54 42.25 50.64 Comparative Example 3 69.72 68.62 70.55 66.90 71.04 Comparative Example 4 63.58 61.06 65.32 72.95 63.16 Comparative Example 5 30.19 29.04 29.56 21.40 24.24 Comparative Example 6 18.95 22.10 20.35 16.75 25.52

[0098] Table 2 Heavy metal resource recovery rate

[0099]

[0100]

[0101] From Table 1-Table 2, we know that:

[0102] Compared with comparative examples 1-6, the present invention adopts examples 1-3 to achieve excellent values ​​for the removal rate and resource recovery rate of heavy metals, and the standard deviations of the removal rates of various heavy metals in examples 1-3 are all less than 0.5%, among which the average removal rates of Tl, Cr, Pb, Cd and Cu are as high as 98.67%, 98.71%, 98.10%, 98.32% and 98.59% respectively; the standard deviations of the resource recovery rates of various heavy metals in examples 1-3 are all less than 2%, among which the average recovery rates of Tl, Cr, Pb, Cd and Cu are 97.13%, 96.50%, 96.89%, 96.51% and 96.53% respectively. The results show that within the parameter range claimed by the present invention, the removal rate and resource recovery rate of heavy metals provided by the present invention can reach excellent values.

[0103] From the comparison between Example 1 and Comparative Example 1, it can be seen that compared with the sleeve-type structure of the inner and outer double helical electrodes used in Example 1, the parallel distribution of the double helical electrodes is not conducive to the formation of a homogenized electric field, which significantly reduces the ability of the quantum dot active electrode 5 to stimulate oxidation and reduction reactions, thereby reducing the removal rate of heavy metals; at the same time, the parallel distribution of the double helical electrodes is not conducive to the fragmentation of the quantum dot active electrode 5 through the electrothermal conversion process, thereby reducing the heavy metal resource recovery rate. Therefore, the sleeve-type structure of the inner and outer double helical electrodes used in Example 1 of the present invention is the main structural basis for ensuring that the electrochemical device of the present invention improves the wastewater heavy metal removal rate and resource recovery rate.

[0104] From the comparison between Example 1 and Comparative Example 2, it can be seen that the lack of carbon quantum dots in the structure of the quantum dot active electrode 5 is not conducive to promoting the generation of oxygen active substances in the electric field, which leads to a significant reduction in the heavy metal removal rate; at the same time, the reduction in the heavy metal removal rate will lead to a reduction in the amount of heavy metals accumulated in the quantum dot active electrode 5, thereby significantly reducing the heavy metal resource recovery rate. Therefore, carbon quantum dots must be added when preparing the quantum dot active electrode 5.

[0105] From the comparison between Example 1 and Comparative Example 3, it can be seen that the lack of iron oxide in the structure of the quantum dot active electrode 5 significantly reduces the heavy metal removal rate. The lack of iron oxide doping in the carbon quantum dots makes them non-magnetic, so that the oxygen active substances with lone pairs of electrons cannot be bound inside the quantum dot active electrode 5 through electromagnetic binding. In addition, due to the reduced heavy metal removal rate, the resource recovery rate of the device for wastewater heavy metals is also significantly reduced. Therefore, electromagnetic binding of active oxygen by doping with iron oxide is the key to improving the removal rate of heavy metals in wastewater and the resource recovery effect.

[0106] From the comparison between Example 1 and Comparative Example 4, it can be seen that the heating reaction of the carbon quantum dots and the oxidized cellulose solution is cancelled, so that the carbon quantum dots and cellulose lack the Schiff base structure connection, which will lead to a significant loss of carbon quantum dots, thereby causing a significant reduction in the heavy metal removal rate and resource recovery rate; at the same time, the loss of carbon quantum dots will cause a significant reduction in the service life of the quantum dot active electrode 5. Therefore, connecting the carbon quantum dots and cellulose into a whole through the Schiff base structure is the key to extending the service life of the quantum dot active electrode 5, and also ensures that the electrochemical device improves the heavy metal removal rate and resource recovery rate.

[0107] By comparing Example 1 with Comparative Example 5, it can be seen that without adding the quantum dot active electrode 5, that is, only relying on starting the DC power supply 4 and the AC power supply 8 to apply the electric field, the heavy metal removal rate and the resource recovery rate will be significantly reduced. By comparing Example 1 with Comparative Example 6, it can be seen that without applying an electric field, that is, only adding the quantum dot active electrode 5, the heavy metal removal rate and the resource recovery rate will also be significantly reduced. This shows that it is necessary to use the quantum dot active electrode 5 in combination with the starting DC power supply 4 and the AC power supply 8 to apply the electric field in order to synergistically improve the heavy metal removal rate and the resource recovery rate.

[0108] In summary, the ring structure of the inner and outer double spiral electrodes adopted in the present invention is conducive to realizing electric field homogenization. The carbon quantum dots in the quantum dot active electrode 5 can produce a large amount of oxygen active substances (such as hydroxyl free radicals, superoxide free radicals and singlet oxygen, etc.) in the homogenized electric field, thereby improving the heavy metal removal rate and resource recovery rate; the iron oxide in the quantum dot active electrode 5 realizes electromagnetic binding of oxygen active substances with lone pair electrons, increases the concentration of oxygen active substances inside the quantum dot active electrode 5, and promotes the removal of heavy metals in wastewater and resource recovery. At the same time, the Schiff base structure strengthens the stability of the carbon quantum dot-cellulose network structure, avoids the precipitation of carbon quantum dots, and prolongs the service life of the quantum dot active electrode 5.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A double-helix electrochemical device, characterized in that: It comprises a reaction chamber (1), an inner spiral electrode (2), an outer spiral electrode (3), a direct current power supply (4), a quantum dot active electrode (5) and a magnetic stirrer (10); A water inlet (1.1) and a feeding port (1.2) are arranged at the top of the reaction chamber (1), and a water outlet (1.3) is arranged on one side of the bottom of the reaction chamber (1); a support column is arranged in the reaction chamber (1) along its axial direction, and the support column is connected to the bottom of the reaction chamber (1); the inner spiral electrode (2) is arranged in the reaction chamber (1) and sleeved on the outer wall surface of the support column; the outer spiral electrode (3) is arranged in the reaction chamber (1), and coaxially sleeved on the outer side of the inner spiral electrode (2) and connected to the inner wall surface of the reaction chamber (1); the outer spiral electrode (3) is connected to the positive electrode of the DC power supply (4), and the inner spiral electrode (2) is connected to the negative electrode of the DC power supply (4); the number of the quantum dot active electrodes (5) is multiple, and they are all arranged in the reaction chamber (1); the magnetic stirrer (10) is arranged at the bottom of the reaction chamber (1); It also includes a recovery tank (6), a screen plate (7), a sludge scraping assembly and an AC power supply (8); The recovery tank (6) is arranged below the reaction chamber (1), and the two are connected via the sieve plate (7); the magnetic stirrer (10) is arranged on the sieve plate (7); the sludge scraping assembly comprises a sludge scraping plate (9), a rotating shaft and a driving member; the rotating shaft is rotatably arranged on the axis of the recovery tank (6), one end of the rotating shaft is arranged in the recovery tank (6), and the other end passes through the bottom of the recovery tank (6) and is connected to the output end of the driving member; the driving member is arranged on the outer side of the bottom of the recovery tank (6); The scraper blade (9) is arranged in the recovery pool (6) and is connected to the rotating shaft; the end of the scraper blade (9) away from the rotating shaft is arranged toward the inner wall of the recovery pool (6) and is in contact with or has a gap with the inner wall of the recovery pool (6); a mud discharge port and an adjustment plate (6.1) for adjusting the opening and closing of the mud discharge port and the size of the opening are arranged on one side wall of the recovery pool (6); the adjustment plate (6.1) is rotatably arranged on the mud discharge port; the positive and negative electrodes of the AC power supply (8) are both connected to the outer spiral electrode (3).

2. The loop-type double-helix electrochemical device according to claim 1, characterized in that: The reaction chamber (1) further comprises a cover plate detachably arranged on the top thereof, the water inlet (1.1) and the feeding port (1.2) are both arranged on the cover plate; an exhaust hole (1.4) is also arranged on the cover plate.

3. The loop-type double-helix electrochemical device according to claim 1, characterized in that: The sieve holes on the sieve plate (7) have a diameter ranging from 0.05 to 0.5 mm.

4. A method for using the loop-type double-helix electrochemical device according to any one of claims 1 to 3, characterized in that: include: Step S1, feeding the quantum dot active electrode (5) into the reaction chamber (1) through the feeding port (1.2); Step S2, adding heavy metal wastewater into the reaction chamber (1) through the water inlet (1.1), controlling the input amount of the quantum dot active electrode (5) to be 1 to 5 g per liter of the heavy metal wastewater; Starting the DC power supply (4) so ​​that the inner spiral electrode (2) and the outer spiral electrode (3) form a homogenized electric field; The magnetic stirrer (10) is started to uniformly disperse the quantum dot active electrode (5) in the heavy metal wastewater, thereby reducing the heavy metal ions in the heavy metal wastewater to form heavy metal precipitates and purified water; wherein the purified water is discharged through the water outlet (1.3), and the heavy metal precipitates are adsorbed in the pores of the quantum dot active electrode (5); Step S3, repeating step S2 for 20 to 30 times, when the quantum dot active electrode (5) is saturated or nearly saturated with the adsorption of heavy metal precipitates, adding a liquid medium into the reaction chamber (1) through the water inlet (1.1); starting the magnetic stirrer (10) to stir until the quantum dot active electrode (5) and the liquid medium are evenly mixed; starting the AC power supply (8) so that the outer spiral electrode (3) generates heat to break up the quantum dot active electrode (5), and the heavy metal precipitates adsorbed by the quantum dot active electrode (5) are released and flow into the recovery tank (6) through the sieve plate (7); settling for 20 to 30 minutes; the liquid medium is discharged through the water outlet (1.3), and the heavy metal precipitates are discharged from the mud outlet through the action of the mud scraping component.

5. The application method according to claim 4, characterized in that: The heavy metal ions in the heavy metal wastewater include at least one of Tl ions, Cr ions, Pb ions, Cd ions and Cu ions; In step S2, the voltage range of the DC power supply (4) is 2 to 5 V / cm, and the operation time is 30 to 60 min; the rotation speed of the magnetic stirrer (10) is 100 to 150 rpm; In step S3, the voltage range of the AC power supply (8) is 220 to 380 V / cm, and the operating time is 1 to 2 hours; the rotation speed of the magnetic stirrer (10) is 200 to 300 rpm; the liquid medium includes pure water, tap water and salt solution; the molar concentration of the salt solution is 0.05 to 0.2 M.

6. The application method according to claim 4, characterized in that: The method also includes preparing the quantum dot active electrode (5), wherein the preparation method is as follows: Step A1, after mixing the prepared carbon quantum dots and the prepared oxidized cellulose solution, add them into a flask, then add acetic acid, heat and react, condense and reflux and stir during the reaction; filter the liquid after the reaction with a dialysis bag, collect the liquid in the dialysis bag, and obtain a carbon quantum dot-cellulose network; Step A2, adding the carbon quantum dot-cellulose network into a dimethyl sulfoxide solution and stirring evenly; then, adding polyvinyl alcohol and heating for reaction, after the reaction is completed, injecting the reaction liquid into a mold, freeze-thawing and forming, to obtain a quantum dot active electrode (5).

7. The application method according to claim 6, characterized in that: In step A1, the method for preparing the carbon quantum dots is as follows: 1.5-2.5 g of citric acid, 50-100 mg of iron oxide and 0.1-0.5 mL of ethylenediamine are added to 15-25 mL of deionized water, and a mixed solution is obtained by ultrasonic treatment; then, the mixed solution is heated at 180-220° C. for reaction for 1-2 hours; after the mixed solution after the reaction is cooled to room temperature, it is dialyzed for 36-48 hours using a dialysis bag with a pore size of 500-1000 Da; the liquid in the dialysis bag is collected and dried to obtain the carbon quantum dots; wherein the ultrasonic time used is 10-30 minutes, and the ultrasonic frequency is 40 KHz; In step A1, the method for preparing the oxidized cellulose solution is as follows: 1-2 g of sodium periodate is dissolved in 90-110 mL of a cellulose solution with a concentration of 2-3 wt%, after mixing in a dark environment, 0.5-1.0 mL of ethylene glycol is added, and the mixture is stirred at 100-150 rpm, and the liquid is collected and filtered through a dialysis bag with a pore size of 8-14 kDa; the dialysis water is replaced once per dialysis day, and the dialysis is performed for 4-7 days, and the liquid in the dialysis bag is collected to obtain the oxidized cellulose solution.

8. The application method according to claim 6, characterized in that: In step A1, when preparing the carbon quantum dot-cellulose network, the amount of the carbon quantum dots is 20 to 50 mg; the amount of the oxidized cellulose solution is 18 to 22 g; the carbon quantum dots and the oxidized cellulose solution are stirred during mixing, the stirring speed is 100 to 150 rpm, and the stirring time is 30 to 60 min; the amount of acetic acid is 0.2 to 0.6 mL; the temperature used during the heating reaction is 80 to 90° C., and the reaction time is 4 to 6 h; the pore size of the dialysis bag used is 8 to 14 kDa, and the dialysis time is 2 to 4 d.

9. The application method according to claim 6, characterized in that: In step A2, when preparing the quantum dot active electrode (5), the amount of the carbon quantum dot-cellulose network used is 6 to 10 g, and the amount of the dimethyl sulfoxide used is 10 to 14 g; when the carbon quantum dot-cellulose network and the dimethyl sulfoxide solution are stirred evenly, the stirring speed used is 100 to 150 rpm, and the stirring time is 30 to 60 min; the amount of the polyvinyl alcohol used is 1.5 to 2.0 g; the temperature used during the heating reaction is 80 to 100° C., and the reaction time is 4 to 6 hours; the temperature used for freeze-thaw is -4 to -20° C.

Citation Information

Patent Citations

  • Device for deeply treating wastewater with low carbon-nitrogen ratio and synchronously removing nitrogen and phosphorus

    CN116750860A